Silencing of Long Non-Coding RNA FGD5-AS1 Inhibits the Progression of Non-Small Cell Lung Cancer by Regulating the miR-493-5p/DDX5 Axis - Fang Cui MD; Peng Luo PhD; Yao Bai BD; Jiangping Meng PhD (Technology in Cancer Research & Treatment, 2021)
Background: Long non-coding RNA FGD5 antisense RNA 1 (FGD5-AS1), identified to be a carcinogenic lncRNA, exhibits a regulatory role in some malignancies including non-small cell lung cancer (NSCLC). The aim of the present research is to decipher the function and underlying mechanism of FGD5-AS1 in progression of NSCLC. Methods: Expression of FGD5-AS1, miR-493-5p and DEAD-box protein 5 (DDX5) in NSCLC tissues and cells was quantified utilizing qRT-PCR. Cell proliferation was assessed by CCK-8 method. Scratch healing test and Transwell assay were used for assaying cell migration and invasion. Expressions of DDX5 and epithelial-mesenchymal transition (EMT)-related proteins were examined by Western blot. Additionally, targeting relationships between FGD5-AS1 and miR-493-5p, miR-493-5p and DDX5 were verified by dual-luciferase reporter gene assay. Results: Expression of FGD5-AS1 in NSCLC tissues and cell lines was up-regulated. Expression of FGD5-AS1 was in association with enlarged tumor size and lymph node metastasis of the patients. Knockdown of FGD5-AS1 led to the inhibition of proliferation, migration, invasion and EMT of NSCLC cells. FGD5-AS1 directly targeted miR-493-5p, while DDX5 was the target of miR-493-5p in NSCLC cells. Additionally, FGD5-AS1 could positively regulate the expression of DDX5 via suppressing miR-493-5p. Conclusion: FGD5-AS1 facilitates the proliferation, migration, invasion and EMT of NSCLC cells by sponging miR-493-5p and up-regulating DDX5.